Unravelling methodologies: a theory building approach - Abdallah, Salam (Curtin University, 2005)
Problem solving methodologies in IS are numerous, varied in objectives and scope, and commonly suffer consequences of deviation and rejection. This research investigates the essence of methodologies in order to understand and to address these consequences. In this thesis, methodologies are treated in a broad sense in order to arrive at a generalisable solution. An integrated research framework was constructed to pursue the solution. The framework is based on my adopted ontological, epistemological and methodological assumptions. The research is considered as an interpretivist single case study using qualitative research methods. A holistic Information Security Methodology was selected for in-depth study. Data were collected from various sources, but primarily from focus groups using 18 participants representing 11 organisations. Data were also collected from the developer of the methodology and two other organisations who were implementing it. Data analysis was based on a grounded approach to arrive at a substantive theory representing a conception of an ideal methodology as perceived by these practitioners. The use of the Hermeneutic circle and the purposely constructed Interrogative Framework were the essential tools for analysis. This conception is believed to hold some of the key factors for reducing the common problems of deviation and rejection of methodologies. The proposed theory is the main contribution of this research, which can be used as a foundation theory to construct and evaluate methodologies. The theory also has been used to propose extensions to existing theories. The core theory consists of basic elements and attributes. Other constructs were also developed to be used as contexts to the theory. In totality these findings provide a rich sphere to examine and understand methodologies.